Perceived Public Trust of the Community in the PNP in District 3 - Sagario, Desley (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceived public trust and confidence in the Philippine National Police (PNP) in the 3rd Congressional District of Negros Occidental, focusing on the effectiveness of police performance and its relationship with community perception. Anchored on Maslow’s Hierarchy of Needs (Fortenbery, 2015), Self-Determination Theory (Andersson Arntén et al., 2016), and principles of community-oriented policing (The Police Community Relations Manual [Revised], 2012), the study employed a descriptive survey research design. A total of 341 participants from Victorias City, Silay City, Talisay City, Murcia, and E.B. Magalona were selected through purposive and stratified sampling. Data were gathered using a researcher-made questionnaire validated by experts and tested for reliability using Cronbach Alpha, and analyzed using frequency, mean, and chi-square. Findings revealed that respondents generally exhibited a high level of trust and confidence in the PNP, with Talisay City showing a very high level. Trust levels varied across localities and were influenced by police visibility, responsiveness, adherence to procedures, community engagement, and perceived effectiveness in crime prevention and investigation. Significant differences in perceptions were observed across cities and municipalities, indicating that police performance and interaction with the community shape public trust. The study concluded that stronger police-community relationships, transparency, and responsiveness enhance public confidence. It recommends strengthening community partnerships, improving accountability, and integrating ethical values in criminal justice education to sustain trust. This study supports Sustainable Development Goal (SDG) 16, which promotes peace, justice, and strong institutions, by highlighting the role of trust in effective policing and governance. Its sustainability impact lies in strengthening institutional credibility, enhancing community cooperation, and promoting accountable and community-oriented policing practices that contribute to long-term social stability.